Sejarah Perbankan Syariah (Dari Konseptual Hingga Institusional) - Devid Frastiawan Amir Sup; Selamet Hartanto (Journal of Islamic Banking, 2020)
The existing Islamic banking institutions are the result of a long journey in the history of Islamic banking. This research aimed to describe the history of Islamic banking, from conceptual to institutional. This research was a follow-up research, the aim of which was to complement the existing discussion of Islamic banking. This research used a qualitative-literature method. The results obtained indicated that the main functions of modern banking have been a part since the time of the Prophet Muhammad, the caliphs, and Muslim dynasties. The formation of Islamic banks was preceded by the prohibition of usury which led to criticism and thoughts from Muslim scholars. Then came the pioneering implementation of the sharia system in Pakistan, Malaysia, India, and Egypt. The development of Islamic banks internationally began with the Foreign Minister's Session organized by the Organization of the Islamic Conference (OIC) which founded the Islamic Development Bank (IDB). Since then, Islamic banks have sprung up in Egypt, Sudan, the Gulf countries, Pakistan, Iran, Malaysia, Bangladesh, Turkey and other countries. In Indonesia, Bank Muamalat Indonesia (BMI) is the first Islamic bank to be established. To date, in Indonesia, commercial banks that carry out Islamic banking operations are classified into Commercial Banks and Sharia Business Units (UUS) Keywords: Bank interest, prohibition of usury, Islamic banking